Division and Effect Evaluation of Fracking Outburst Elimination Zones in Surface Extraction Wells of Coalbed Methane - Jianbao Liu; Zhimin Song; Bing Li; Jiangang Ren; Hongyan Zhang; Nuo Cheng (Geofluids)
Surface hydraulic fracturing is an important measure for increasing reservoir permeability, which has advantages such as engineering safety and a large impact range and can be implemented ahead of the mine’s underground engineering. However, its underground outburst reduction range and effect are rarely reported, and there is a lack of connection with underground fracturing wells. Taking coalbed methane wells in the Lu’an Mining Area as an example, underground observation, microseismic monitoring, and numerical simulation methods were used to study the fracturing range and outburst control effect of surface wells. The fracturing zone of coalbed methane wells is approximately elliptical in shape, with the main fractures extending along the direction of the maximum horizontal principal stress. It can be divided into five zones: sand laying zone (radius of 140~150 m), fracture propagation zone (radius of about 180 m), fracturing fluid permeability zone (width of about 1 m), gas surge zone (width of 2~3 m), and final desorption zone (width of about 2 m). The stress around the fracturing zone increases along the direction of maximum and minimum principal stresses, while the stress value within the zone decreases, with a range of approximately 5~20% of the original geostress. The outburst reduction index Δh2 in the fracturing zone significantly decreased after fracturing. The percent of Δh2 (< 150 Pa) increased from 38.3% to 100% after fracturing. A model for evaluating the effectiveness of surface fracturing and outburst prevention was proposed, and the model was used in Tunliu Mine. The results showed that the standard-reaching rate of extraction was high, and the danger of outburst could be completely eliminated. The research results can provide a reference for the arrangement of the coalbed methane wells and can also provide effective guidance for outburst prevention and control work during mining and excavation on a more macro scale. It provides a new idea and method for making up for the shortcomings such as the small impact range and safety hazards of underground fracturing.